THE ROLE OF HIPPOTHERAPY IN THE REHABILITATION OF PATIENTS WITH SELECTED CENTRAL NERVOUS SYSTEM DISORDERS: A NARRATIVE REVIEW - Julia Kwiecińska; Władysław Hryniuk; Jacek Sitkiewicz; Alicja Toczyłowska; Mateusz Muras; Łukasz Bialic; Lidia Mądrzak; Marta Korchowiec; Wiktor Chrzanowski; Katarzyna Krzyżanowska (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Hippotherapy is an equine-assisted intervention gaining popularity to support the rehabilitation of patients with neurological disorders. By applying the horse’s rhythmic movement, it aims to improve motor function, postural control, and overall quality of life. In addition to traditional therapy with live animals, mechanical simulators are now also employed. Neurological conditions such as cerebral palsy, stroke, and multiple sclerosis often lead to functional impairments that may benefit from complementary therapies. Aim: The aim of this review is to evaluate the effectiveness of hippotherapy in improving physical and psychosocial outcomes in patients with selected central nervous system disorders. Review methods: All data were collected from publicly available sources. This article’s databases were accessed via PubMed, Google Scholar, and other scientific databases in May 2025. Conclusions: Hippotherapy appears to be an effective complementary method in the rehabilitation of patients with neurological disorders, offering improvements in motor function, balance, posture, and psychosocial well-being. Both traditional and simulator-based forms show therapeutic potential. However, variability in study quality, small sample sizes, lack of standardization, and high costs limit the strength of current evidence. Further high-quality research is needed to confirm its effectiveness and cost-efficiency in clinical practice.